PENGEMBANGAN MEDIA PEMBELAJARAN SIMULASI INTERAKTIF BERBASIS GDEVELOP PADA MATERI PROSEDUR MENCETAK DOKUMEN KELAS X MPLB DI SMK PGRI 1 TULUNGAGUNG - Asmoro Bayu Aji, Tri; Haris Indrakusuma, Abdul; Panggayuh, Vertika (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to develop GDevelop-based interactive simulation learning media for document-printing procedures and determine its feasibility for Grade X Office Management and Business Services students at SMK PGRI 1 Tulungagung. The study employed research and development using the ADDIE stages: analysis, design, development, implementation, and evaluation. The product was created with GDevelop 5, exported as HTML5, and packaged as an Android application. It contained learning outcomes, instructional objectives, materials, videos, quizzes with automatic feedback, reflection, and structured navigation. Participants comprised one media expert, one subject-matter expert, six students in a small-group trial, and 30 students in a large-group trial. Data were collected through observation, interviews, expert-validation questionnaires, and student-response questionnaires, then analyzed using descriptive percentages. Initial media validation reached 73.61%; after revisions to color, typography, imagery, navigation, quiz functions, loading, and responsiveness, it increased to 99.07%. Subject-matter validation rose from 95.00% to 100%. The small- and large-group trials yielded 98.94% and 95.55%, respectively. These findings place the product in the highly feasible category for classroom support and independent study. Because the study measured feasibility and user responses rather than learning gains, further experimental testing is required to establish effectiveness.